Ge Enrichment of Ge–Sb–Te Alloys as Keystone of Flexible Edge Electronics - Sabrina Calvi; Marco Bertelli; Sara De Simone; Francesco Maita; Simone Prili; Adriano Diaz Fattorini; Fabio De Matteis; Valentina Mussi; Flavia Righi Riva; Massimo Longo; Fabrizio Arciprete; Raffaella Calarco (Advanced Electronic Materials)
Abstract Edge computing architectures are intended to store and process data nearby the sensor, while ensuring fast and safe data processing, low power consumption and cost minimization. The stability, mechanical flexibility, huge computational and storage requirements needed for these applications are beyond the capability of current embedded devices. Memories based on phase‐change materials have the potential to overcome these issues. However, their behavior on flexible substrates is yet to be understood and alloys owning the required key features still need to be proposed. With this work, it is demonstrated that Ge–Sb–Te (GST) alloys are large‐area scalable and directly processable on flexible substrates, while their large resistance contrast enables the prospect of multilevel data encoding. Remarkably, the Ge enrichment acts as both thermal and mechanical stabilizer within the alloy. The highlighted features of Ge‐enriched GST alloys show their potential as new active materials for the most demanding flexible edge electronics applications.